O ESTUDO DA COMPLEXIDADE EM PROGRAMAS DE PÓS-GRADUAÇÃO NO BRASIL: UMA ANÁLISE A PARTIR DO PENSAMENTO COMPLEXO E SUA RELAÇÃO COM A EDUCAÇÃO - Ruiz, Alonso Benjamin Muñoz (2016)
The following work has as objective to analyze the main characteristics of the production of theses and dissertations about the Theory of Complexity in Brazil in the years of 2011 and 2012, as a tool that can build a reference of study to the interested in the subject. Throughout this process was researched data about the production of theses and dissertations related to the paradigm of complexity in Brazil, deepening in the analysis of those works in the area of education. It was realized a registration of the main field of application of such works. By the technique of document analysis it was intended to recognize the major disciplinary association that emerged starting from this new view to the construction of a new of organization of the scientific knowledge, as well as the principal exponents quoted about this theory in the selected works. For such endings, a research was realized in the CAPES bank of theses with three main criteria of search: “Theory of Complexity”, “Paradigm of Complexity” and “Complex Thinking”. The result was processed by spreadsheet of the Microsoft Excel. The results highlighted a strong association between the theory of complexity and the education, mainly in reference to the formation of teachers under new views and pedagogical practices, however, exist a wide variety of knowledge, in which the theory converses. The most used methodological technique was the bibliographical research. On the other hand, most of the researches derive in diagnoses about specific situations.